A construção de conhecimentos e saberes dos gestores de cursos contemporâneos de graduação: análise de uma experiência da rede SENAC - Marins, Hiloko Ogihara (2008)
Today, the world of work faces deep changes in all areas of knowledge and requires higher education institutions to educate people and professionals in order that they can deal with the new reality and new professional fields. To deal with that growing demand, the educational institutions must rely on educational managers who have a view to the future, theoretical basis and professional experience in leadership to carry out new projects, new courses and new educational researches to make autonomous people who will seek efficiency in their professional performance. The success of this business is based on the relationships among people during the teaching and learning process. Therefore, the present work aims at investigating the managers academic and professional journey and checking what contributions they bring to educational work management of contemporary college curses since they concern the new perspectives on people management. The main authors who support the present work are: Abdalla, Aguiar, Alonso, Feldmann, Ferreira, Freire, Masetto, Tardif, Lessard, Shulman, Sacristán, Dutra, Tachizawa et al., Bateman/Snell, Motta, Aquino, Kwasnicka, Maximiano, Covey, Bennis, Bergamini and Coda. The methodology was based on qualitative approach and book references to understand the past, present and future of people management and also on semi-structured interviews with the contemporary college managers of Centro Universitário Senac São Paulo. The analysis of collected data showed the results of field research in which the managers emphasize the importance of academic education, the understanding of management processes, the organizational changes, the knowledge of other cultures, different personal and professional experiences for a suitable relationship between teacher and student, managers and partners, managers and superiors and all people who are involved in professional education within a respectful and ethical relationship